Syphilis predicts HIV incidence among men and transgender women who have sex with men in a preexposure prophylaxis trial - Marc M. Solomon (2018)
© The Author 2014. Background. Syphilis infection may potentiate transmission of human immunodeficiency virus (HIV). We sought to determine the extent to which HIV acquisition was associated with syphilis infection within an HIV preexposure prophylaxis (PrEP) trial and whether emtricitabine/tenofovir (FTC/TDF) modified that association. Methods. The Preexposure Prophylaxis Initiative (iPrEx) study randomly assigned 2499 HIV-seronegative men and transgender women who have sex with men (MSM) to receive oral daily FTC/TDF or placebo. Syphilis prevalence at screening and incidence during follow-up were measured. Hazard ratios for the effect of incident syphilis on HIV acquisition were calculated. The effect of FTC/TDF on incident syphilis and HIV acquisition was assessed. Results. Of 2499 individuals, 360 (14.4%) had a positive rapid plasma reagin test at screening; 333 (92.5%) had a positive confirmatory test, which did not differ between the arms (FTC/TDF vs placebo, P = .81). The overall syphilis incidence during the trial was 7.3 cases per 100 person-years. There was no difference in syphilis incidence between the study arms (7.8 cases per 100 person-years for FTC/TDF vs 6.8 cases per 100 person-years for placebo, P = .304). HIV incidence varied by incident syphilis (2.8 cases per 100 person-years for no syphilis vs 8.0 cases per 100 personyears for incident syphilis), reflecting a hazard ratio of 2.6 (95% confidence interval, 1.6-4.4; P < .001). There was no evidence for interaction between randomization to the FTC/TDF arm and incident syphilis on HIV incidence. Conclusions. In HIV-seronegative MSM, syphilis infection was associated with HIV acquisition in this PrEP trial; a syphilis diagnosis should prompt providers to offer PrEP unless otherwise contraindicated.